Communication in uncertain times : how organizations deal with issues, risks and crises - Einwiller, Sabine; Seiffert-Brockmann, Jens; Romenti, Stefania; Valentini, Chiara (Advances in public relations and communication management, 2024)
Technological developments and globalization have not only propelled societal progress, but they have also ushered in significant challenges and risks that continually demand responses and adaptability from today's dynamic and complex societies. In this context, organizations find themselves grappling with the need to navigate and manage these challenges effectively. For public relations scholars and practitioners, this reality poses crucial questions concerning communication strategies and their impact in today's risk societies. Communication in Uncertain Times explores how different organizations, from private to governmental and non-profit, deal with issues, risks, and crisis situations through communication. Questions include how to address risks and issues to decrease uncertainty, how to negotiate conflicts, and what types of roles professionals and non-professional communicators assume in times of risk, uncertainty, and crises. The chapters comprise selected contributions to the 2022 Annual Congress of the European Public Relations Education and Research Association (EUPRERA) hosted in Vienna, Austria, by the University of Vienna and the Vienna University of Economics and Business. Advances in Public Relations and Communication Management (APCRM) is a publication of the European Public Relations Education and Research Association (EUPRERA). Each volume includes contributions from EUPRERA's annual congress and follow the theme of each event.